Cuscuta chinensis and C. campestris Attenuate Scopolamine-Induced Memory Deficit and Oxidative Damage in Mice - Lin, Ming-Kuem; Lee, Meng-Shiou; Huang, Hui-Chi; Cheng, Tun-Jen; Cheng, Yih-Dih; Wu, Chi-Rei (Molecules (Basel, Switzerland), 2018)
The seeds of Cuscuta chinensis Lam. and C. campestris Yuncker have been commonly used as Chinese medical material for preventing aging. Our previous studies have found that C. chinensis and C. campestris possess anti-inflammatory activities in rodents. However, their other biological activities, such as memory-improving properties, have not yet been explored. In the present study, we examined the memory-improving effects of the extracts of C. chinensis and C. campestris on scopolamine (SCOP)-induced memory deficit and explored their underlying mechanism in mice. Both Cuscuta species improved SCOP-induced memory deficits in the passive avoidance test, elevated plus-maze, and spatial performance test of the Morris water maze in mice. In addition, compared with mice injected with SCOP, mice pretreated with both Cuscuta species stayed for a longer time on the platform for the probe test of the Morris water maze. Moreover, both Cuscuta species reduced brain acetylcholinesterase activity and malondialdehyde levels that were increased by SCOP, and the species restored the activities of antioxidant enzymes (superoxide dismutase and catalase) and the levels of glutathione that were decreased by SCOP in the brains of mice. Both Cuscuta species further decreased brain interleukin-1β and tumor necrosis factor-α levels that were elevated by SCOP. We demonstrated that both Cuscuta species exhibited a protective activity against SCOP-induced memory deficit, cholinergic dysfunction, oxidative damage, and neuroinflammation in mice, and C. campestris has better potential than C. chinensis. In addition, we provided evidence that the seeds of C. campestris can be used as Cuscutae Semen in Traditional Chinese Medicine.